Best Answer

if this question is -6 times 3 plus 15 then = -21

if its -6 plus 3 plus 15 then = 12

if its -6 times 3 plus 1.5 then = -16.5

if it is -6 plus 3 plus 1.5 = -1.5

Study guides

☆☆

Q: -6x plus 3 plus 1 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5

The value of X in the equation 2x-1-6 5 plus 6x is -3.

y=(6x-5)/3

6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3

-3*6x+5/8=6x-1 * (-3*(6x+5))/8?If this is your question, then:LHS = -3 * 6x + 5/8 = -18x + 5/8RHS = 6x - 1 * (-18x-15)/8 = 6x + (18x+15)/8 = 48x/8 + 18x/8 + 15/8 = 66x/8 + 15/8-18x + 5/8 = 66x/8 + 15/866x/8 + 18x = 15/8 - 5/8210x/8 = 10/8210x = 10x = 10/210 = 1/21

Related questions

Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5

6x + 3 = 2x + 5 4x = 2 x=1/2

The value of X in the equation 2x-1-6 5 plus 6x is -3.

If: 6x-4+7 = 5 Then: x = 1/3

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

y=(6x-5)/3

6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3

-3*6x+5/8=6x-1 * (-3*(6x+5))/8?If this is your question, then:LHS = -3 * 6x + 5/8 = -18x + 5/8RHS = 6x - 1 * (-18x-15)/8 = 6x + (18x+15)/8 = 48x/8 + 18x/8 + 15/8 = 66x/8 + 15/8-18x + 5/8 = 66x/8 + 15/866x/8 + 18x = 15/8 - 5/8210x/8 = 10/8210x = 10x = 10/210 = 1/21

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

x2 + 6x + 5 can be factored into (x+1) (x+5)

24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)

34x + 72 is the answer to the equation 12 plus 6x-4 5 plus 2 3x-1.